(untitled) (UNED Research Journal, 2014)
This is a preliminary species list for the mammals of Nombre de Dios National Park (PNND) based on 5 visits to 8 sampling sites in the following systems: a) low montane wet forest, b) Sub tropical wet forest, c) within the limits of these forests, and d) in Mangrove Forests of two coastal lakes. We recorded 43 species belonging to 6 orders: Marsupialia, Xenarthra, Chiroptera, Primates, Perissodactyla, and Rodentia. The order with more families was Rodentia (6 = 35%), followed by Chiroptera with (5 = 29%). Nine species are in CITES, three in Appendix I, two in Appendix II and three in Appendix III. We recorded the bat Hylonycteris underwoodi for the first time for Honduras and an endemic species from Central America Rhogeessa menchaue inhabits the park. There are 24 new records for Atlantis.